Contributions of an artistic educational program for older people with early dementia: An exploratory qualitative study. (July 2013) - Ullán, Ana M.; Belver, Manuel H.; Badía, Marta; Moreno, Carmen; Garrido, Eugenio; Gómez-Isla, José; Gonzalez-Ingelmo, Elena; Delgado, Juan; Serrano, Isabel; Herrero, Carmen; Manzanera, Paloma; Tejedor, Laura
Objective: To describe a contemporary artistic educational program based on photographic cyanotype techniques and to present the results of the program carried out with older people with early dementia. We determined whether these people could participate in the program, their viewpoint about it, and what this program could contribute to their experience. Method: Twenty-one people diagnosed with mild or moderate dementia participated in a series of artistic education workshops. While conducting the workshops, participant observation was carried out, and the participants' engagement was assessed. Upon completing the series, five focus groups were held with the participants with dementia, and another focus group with their professional caretakers. Results: We observed the participants' high level of commitment to the activity and their interest in learning new things. We also observed the participants' satisfaction during the creative process and with their results. The artistic activities not only reinforced the feelings of capacity of the participants with early dementia but also transmitted a positive image of them. Conclusions: Dementia was not an obstacle to participation in the program, which was an opportunity for creativity, learning, enjoyment, and communication for people with dementia. In the authors' opinion, facilitating access to art and artistic education to people with early dementia can contribute to enforcing their rights and to improving the care system.